On Nano β_pc-Open Set and Some of Its Application - Saleh, Saif; Jamil Mahmoud Jamil (ASJ - Academic Science Journal, 2025)
. The major objective of this work is to establish and assemble a new type of Nano pre-open termed a Nano- open set, which is an advanced form of Nano pre-open. Additionally, we identify a class of Nano -open sets in terms of Nano topology elements. Furthermore, this has a number of given properties. In this paper, we introduce a completely novel kind of Nano continuity that we’ve labeled Nano -continuous functions, and we address many of its characterizations.